Ngopi Santai: Edukasi Psikologis tentang Tantangan dan Strategi Coping Generasi Z di Dunia Kerja - Dwi Anggraini Rahman; Reva Villya Ayu Priyanti; Erika Nurazizah (Medan Resource Center, 2026)
Generation Z faces various psychological challenges in the modern workplace, including anxiety, mental pressure, and difficulties in adapting to conventional work norms. This community service activity aimed to provide participants with an understanding of workplace challenges and effective coping strategies for dealing with them. The method employed was a Focus Group Discussion (FGD) integrated with a positive psychology-based group counseling approach. The activity involved students, fresh graduates, and young Generation Z professionals. The results demonstrated an improvement in participants’ understanding of Generation Z characteristics in the workplace, their ability to identify psychological challenges encountered in professional settings, and their mastery of effective stress-coping strategies, as indicated by a 73.8% increase in cognitive scores. In addition, the Ngopi Santai activity proved that an informal and relaxed atmosphere could enhance participants’ openness in discussing psychological issues and sharing their experiences related to workplace adaptation. These findings indicate that an informal psychoeducational approach can effectively strengthen participants’ psychological preparedness in facing workplace challenges. Therefore, this program is recommended to be continued through regular mentoring and individual counseling for participants requiring further assistance.